The state of solar PV and performance analysis of different PV technologies grid-connected installations in Hungary. (May 2021) - Atsu, Divine; Seres, Istvan; Farkas, Istvan
Abstract: The first part of this paper assesses the state of solar PV in Hungary, considering available government support in terms of policies, targets, and the conducive environment for exploiting solar PV. The study further analyses a 15-year-old 9.6 kWp roof-mount grid-connected solar PV system whiles comparing its performance parameters with similar installations in the sub-region. Findings show that Hungary possesses a relatively high solar energy resource which has not been exploited as expected compared to most of the countries in the European sub-region. Hungary has in place the necessary policies and diverse incentives for the adaptation of renewable energy sources as required by the European Union. However, complexities in land acquisition and legal definitions of PV systems still exist. The installed solar PV capacity in Hungary as of 2018, is 790 MWp. The target of the Hungarian Renewable Action Plan is to have 14.65% of the electricity demand supplied by renewable energy sources by 2020. The experimental study shows that the total energy output from the 9.6 kWp system is 8838.95 kWh for the year of assessment. The energy outputs for the subsystems are 3761.98 kWh, 2608.88 kWh and 2468.10 kWh for ASE (pc-Si), DS2 (a-Si) and DS1 (a-Si) respectively. The annual sub-system efficiencies are 9.8%, 2.9% and 2.8% for ASE (pc-Si), DS2 (a-Si) and DS1 (a-Si) respectively. Thus, 42.6% of energy fed into the grid was from the ASE (pc-Si) system, 29.5% and 27.9% from the DS2 (a-Si), and DS1 (a-Si) respectively. Highlights: The state of solar PV in Hungary and the related policies for adaptation reviewed. Long term assessment of different grid-connected solar PV systems studied. Performance ratios of studied PV systems range between 55.6 and 77.2%. System efficiencies vary from 2.8% to 11.5%.